Blockade of the P2Y2 Receptor Attenuates Alcoholic Liver Inflammation by Targeting the EGFR-ERK1/2 Signaling Pathway - Liu ZN; Su QQ; Wang YH; Wu X; Lv XW (Dove Medical Press, 2022)
Zhen-Ni Liu,1- 3,* Qian-Qian Su,4,* Yu-Hui Wang,1- 3,* Xue Wu,1- 3 Xiong-Wen Lv1- 3 1Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, Anhui Institute of Innovative Drugs, School of Pharmacy, Anhui Medical University, Hefei, People's Republic of China; 2The Key Laboratory of Anti-Inflammatory and Immune Medicines, Ministry of Education, Hefei, People's Republic of China; 3Institute for Liver Diseases of Anhui Medical University, Hefei, People's Republic of China; 4Department of Pharmacy, the First Affiliated Hospital of Anhui Medical University, Hefei, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiong-Wen Lv, School of Pharmacy, Anhui Medical University, 81 Mei Shan Road, Hefei, Anhui Province, 230032, People's Republic of China, Email xiongwen_lv2019@163.comPurpose: It is well known that inflammation plays a key role in complex pathological progressions of alcohol-associated liver disease (ALD). To date, effective therapy for ALD is lacking. P2Y2 receptor (P2Y2R), a G protein-coupled P2Y purinergic receptor, represents a novel pharmacological target in many inflammations.Methods: The alcohol-associated liver injury and inflammation mouse model was established. The effect of P2Y2R on alcohol-induced liver injury and inflammation was evaluated using quantitative real-time PCR, Western blot and immunohistochemical assay. An alcohol-stimulated (100 mmol/L, for 24 h) AML-12 cell model was established. Different agonists, antagonists and P2Y2R siRNA were used to explore the possible mechanisms of P2Y2R.Results: In vivo, results showed that the hepatoprotective effect of P2Y2R blockade by significantly suppressed liver structural abnormalities and lipid infiltration, and decreased levels of ALT/AST and TNF-α/IL-1β in the high dosage group of suramin (20 mg/kg) compared to control diet (CD)-fed mice. At the same time, we found that alcohol feeding promoted the phosphorylation of EGFR and ERK1/2, both of which were effectively inhibited by suramin (20 mg/kg). In vitro, suramin or P2Y2R silencing effectively inhibited the phosphorylation of EGFR and ERK1/2, similar to the down-regulated effects of their corresponding inhibitors (EGFR inhibitor AG1478 and ERK1/2 inhibitor U0126) accompanied by reduced levels of TNF-α and IL-1β compared to alcohol-induced AML-12 cell. In addition, we found that silencing P2Y2R attenuated the apoptosis of hepatocyte.Conclusion: Our findings suggest that P2Y2R regulates alcoholic liver inflammation by targeting the EGFR-ERK1/2 signaling pathway and plays an important role in hepatocyte apoptosis, which may provide new ideas for the development of methods to treat ALD.Keywords: P2Y2 receptor, alcoholic liver inflammation, EGFR, ERK1/2